ENHANCING THE EFFECTIVENESS OF TEACHER TRAINING PROGRAMS: A CASE STUDY ON SPECIALIZED SUBJECTS IN FOREIGN LANGUAGE EDUCATION (Web of Teachers: Inderscience Research, 2024)
This article presents a case study that investigates the effectiveness of teacher training programs in improving the delivery of specialized subjects in foreign language education. The article focuses on a specific program at a reputable university, examining the challenges faced by teachers and identifying strategies for enhancement together with highlighting the importance of subject-specific knowledge, integration of innovative teaching techniques, technology integration, and collaboration and professional development. The findings offer practical recommendations for improving teacher training programs to better equip educators in delivering specialized subjects effectively and provides valuable insights for institutions and educators seeking to enhance the effectiveness of their teacher training programs in foreign language education.